Necessary Suffering and Lewisian Theism - Collier, Matthew James (Sophia, 2022)
One can readily conceive of worlds of horrendous, gratuitous suffering. Moreover, such worlds seem possible. For classical theists, however, God, amongst other things, is perfectly good. So, the question arises: for classical theists are such evil worlds possible? Many classical theists have said no. This is the modal problem of evil. Herein, I discuss a related problem: the problem of evil worlds for Lewisian theism. Lewisian theism is the conjunction of Lewis’s modal realism and classical theism, and a leading Lewisian theist, Almeida, thinks that Lewisian theists should admit the existence of on-balance evil worlds. I do not. Herein, I present a dilemma for Almeida: either give up God’s sovereignty and the reductionist account of modality or make God blameworthy for evil.